Microfoundations of open innovation: the creation of open innovation management organizations - Bruno, Rondani (2012)
Since Chesbrough (2003) first coined the concept of open innovation it has attracted a growing attention both in academia and in practice. Despite the increasing efforts to explore open innovation, many questions remain unanswered. Academic research has spread its focus into different topics such as innovation management, business strategy, organizational behavior and public policies. Practitioners, on the other hand, have been exploring the concept of open innovation in diversified ways. Taking into account the variability of open innovation practices, this study seeks to provide microfoundations for open innovation by adopting the effectuation theory. Effectuation theory was originally developed in the field of entrepreneurship research and can be defined as a set of teachable and learnable decision-making principles that together form an overall logic that expert entrepreneurs are observed to employ in situations of uncertainty in order to create new ventures and new markets. (SARASVATHY, 2001; 2008). We have shown that the effectuation theory has the strength to provide strong contribution to build a consistent micro level conceptual basis for open innovation practices. By performing an extensive case study of an open innovation management organization dedicated to foster collaborations between Brazil and Sweden, we examine the decision-making processes of 13 expert R&D and innovation managers representing eight different entities involved in the startup of this new organization. As a result of our research we identified and described a decision-making methodology used by expert innovation managers involved in the creation of an open innovation management organization. The research insights that emerged from this case study enabled us to develop a decision-making framework based on effectuation and open innovation theories that could support managers to start-up new organizations dedicated to open innovation.